The consultant CONUNDRUM - PERCHTHOLD, Gordon (Institutional Knowledge at Singapore Management University, 2010)
The article discusses the techniques of managers in the selection of consultants and consulting firms for the requirement of specific expertise. It suggests several approaches in the selection of an appropriate consultant, including the use of web sites to browse the services of consulting firms. It mentions the availability of decision support for a specific type of project which uses third-party reviewers to present the list of possible consulting firms that could be applied to the area of expertise needed. It cites the examples of activities which aid in the assessment of the capabilities of consultants including in-depth workshop, reference check, and follow-up questions.